2011
DOI: 10.1021/jp207585j
|View full text |Cite
|
Sign up to set email alerts
|

Hole Transport in Triphenylamine Based OLED Devices: From Theoretical Modeling to Properties Prediction

Abstract: For the series of para-substituted triphenylamines, optimized geometries, HOMO and LUMO energy levels, ionization potentials Ip, reorganization energies for hole transport λ(+), and frontier orbital contours have been calculated by means of ab initio computations. Relationships between them and the Hammett parameter are presented. According to calculations, electron releasing substituents increase the HOMO and LUMO energies of TPA, while electron withdrawing ones decrease it. This behavior is reflected in subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
128
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(131 citation statements)
references
References 52 publications
2
128
0
1
Order By: Relevance
“…The bond length of the C 2 -N bond increased slightly from 1.400 to 1.429Å. The central moiety retains planarity, indicating that there is little affect on structural stability as the Scheme 2 Sketch of triarylaminehelicene (TAH) derivatives in this study using DFT at B3PW91/6-311G (2d, 2p) ++ level of theory optimized cationic geometries show only small structural changes compared to the natural molecules, which are close to triarylamine [75]. From plots of change in interplanar angle versus the Hammett parameter, we observed that, upon extraction of one negative charge from the system, the amplitude of structural modification from TAH derivatives increases with electron-donating substituents compared to TAH derivatives with electron-withdrawing substituents, signifying an apparent substitution effect on the TAH derivatives (see Fig.…”
Section: Geometrymentioning
confidence: 80%
See 2 more Smart Citations
“…The bond length of the C 2 -N bond increased slightly from 1.400 to 1.429Å. The central moiety retains planarity, indicating that there is little affect on structural stability as the Scheme 2 Sketch of triarylaminehelicene (TAH) derivatives in this study using DFT at B3PW91/6-311G (2d, 2p) ++ level of theory optimized cationic geometries show only small structural changes compared to the natural molecules, which are close to triarylamine [75]. From plots of change in interplanar angle versus the Hammett parameter, we observed that, upon extraction of one negative charge from the system, the amplitude of structural modification from TAH derivatives increases with electron-donating substituents compared to TAH derivatives with electron-withdrawing substituents, signifying an apparent substitution effect on the TAH derivatives (see Fig.…”
Section: Geometrymentioning
confidence: 80%
“…The molecular orbitals contributions are important in determining the charge-separated states of TAH derivatives. To create an efficient charge-separated state, the HOMO must be localized on the donor subunits and LUMO on the acceptor subunits [75]. In the TAH(2) derivative, the HOMO comprises both helical conjugate and substituent, which is indicative of enhanced CT efficiency.…”
Section: Electronic Energy Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both compounds provided a single absorption 25 band at 306 nm, which we attribute to the energy level of their triphenylamine functional groups. 16,42,43 The band gap energies (E g ) of the films of TPABZ and P-TPABZ, obtained from their onset absorption wavelengths in the UV-Vis absorption spectra, were 3.49 and 3.48 eV, respectively (Eg = 1240/λ). Fabrication of 30 multilayer OLEDs and PLEDs through solution-processing requires a film to be insoluble in the solvent used for the subsequent deposition process.…”
Section: Thermal Properties Of Tpabz and P-tpabzmentioning
confidence: 99%
“…15 The triphenylamine functional group has been investigated thoroughly; it is considered a promising HITL material because of its appropriate energy level and good hole injection/transporting ability. 16 The small 65 molecules for OLED devices are regularly incorporated using high-vacuum vapor deposition, which allows the fabrication of well-defined multilayers with relatively simple structures. Small organic compounds also can be purified, through crystallization or sublimation, to a high degree prior to deposition.…”
Section: Introductionmentioning
confidence: 99%